2010
DOI: 10.1007/s11064-010-0133-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of a 6-Hydroxydopamine Model of Parkinson’s Disease

Abstract: Convection enhanced delivery of 6-hydroxydopamine (6-OHDA) to the rat striatum results in a model of Parkinson's disease. An important feature of this unilateral model is the progressive loss of dopaminergic (DA) neurons over the course of several weeks. To improve the understanding of this model, gene expression changes in the substantia nigra, which contains the DA neuron cell bodies, and the striatum, which contains the DA neuron synaptic terminals, were examined using DNA microarrays. Samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Reductions in TH mRNA levels after 6‐OHDA lesion have been previously reported (Na et al ., ), and during the cell size analysis we again noted a reduction in the level of TH expression on the lesioned side of the brain. We thus attempted to quantify this by comparing the difference in the intensity of TH expression using fluorescent staining in the SNpC on the lesioned side of the brain when compared with the unlesioned side.…”
Section: Resultsmentioning
confidence: 99%
“…Reductions in TH mRNA levels after 6‐OHDA lesion have been previously reported (Na et al ., ), and during the cell size analysis we again noted a reduction in the level of TH expression on the lesioned side of the brain. We thus attempted to quantify this by comparing the difference in the intensity of TH expression using fluorescent staining in the SNpC on the lesioned side of the brain when compared with the unlesioned side.…”
Section: Resultsmentioning
confidence: 99%
“…For example, when 6-OHDA is injected into the striatum, microglial activation appears to be more robust within the striatum than in the SN at 7 and 28 days after the lesion (Armentero et al, 2006). In contrast, others (Na et al, 2010) reported that intrastriatal 6-OHDA resulted in an increase in inflammatory-related gene expression within both the striatum and the SN 7 days post-lesion, an effect that persisted within the SN for 14 days. Taken together, data from multiple studies suggest that inflammatory processes play a secondary but important role in 6-OHDA-induced nigral degeneration.…”
Section: Role Of Microglia Activation In Rodent Models Of Nigral Dopamentioning
confidence: 86%
“…In that regard, rats treated with unilateral intrastriatal 6-OHDA showed temporarily increased levels of reactive nitrogen and oxygen species markers in the striatum, peaking between 25 min to 2 h after neurotoxin, and returning to near-baseline values within 7 days [53]. mRNA microarray and positron emission tomography (PET) with the radioligand [3H]PK11195 (a marker of microglial activation) confirmed these transient inflammatory changes, demonstrating a return to baseline values within 28 days post-6-OHDA [54,55]. …”
Section: Discussionmentioning
confidence: 99%